Characterization of IncN plasmids carrying bla CTX-M-1 and qnr genes in Escherichia coli and Salmonella from animals, the environment and humans - Dolejska, Monika; Villa, Laura; Hasman, Henrik; Hansen, Lars; Carattoli, Alessandra (The Journal of antimicrobial chemotherapy, 2013)
OBJECTIVES: The aim of the study was to characterize a collection of Escherichia coli and Salmonella harbouring qnr and bla(CTX-M-1) genes on IncN plasmids isolated from humans, food-producing, companion and wild animals, and the environment from six European countries. METHODS: Nineteen IncN plasmids were compared using restriction fragment length polymorphism (RFLP), plasmid multilocus sequence typing (pMLST) and hybridization with repN, qnrS1, qnrB19 or bla(CTX-M-1) probes. Plasmids pKT58A and pHHA45 were sequenced using the 454-Genome Sequencer FLX platform on a library constructed from plasmid DNA purified from the respective E. coli transformants. RESULTS: Three types of IncN plasmids carrying bla(CTX-M-1), qnrS1 and qnrB19 genes were identified in strains isolated from the Czech Republic, Poland, Slovakia, Denmark, Italy and the Netherlands, corresponding to pMLST sequence type (ST) 1, ST3 and ST8, respectively. Related plasmids circulating in human and animal isolates were identified. Complete nucleotide sequences of the ST1 pHHA45 plasmid carrying bla(CTX-M-1), isolated from E. coli from pigs in Denmark, and the ST3 pKT58A plasmid harbouring qnrS1, identified in E. coli from a water bird, were obtained. CONCLUSIONS: Our results demonstrated wide distribution of specific IncN plasmids disseminating bla(CTX-M-1) and qnr genes among animals and humans in Europe.
Keywords: polymorfismus délky restrikčních fragmentů; lidé; Plasmids; bakteriální geny; mikrobiologie životního prostředí; beta-laktamasy; Evropa; beta-Lactamases; DNA bakterií; proteiny z Escherichia coli; Bacterial Infections; multilokusová sekvenční typizace; Humans; plazmidy; Genes, Bacterial; Environmental Microbiology; Nucleic Acid Hybridization; DNA, Bacterial; Escherichia coli; Polymorphism, Restriction Fragment Length; Escherichia coli Proteins; zvířata; hybridizace nukleových kyselin; molekulární sekvence - údaje; Animals; Multilocus Sequence Typing; Molecular Sequence Data; Europe; bakteriální infekce; Salmonella